2021
DOI: 10.1039/d0nr08300c
|View full text |Cite
|
Sign up to set email alerts
|

Large-scale investigation of the effects of nucleobase sequence on fluorescence excitation and Stokes shifts of DNA-stabilized silver clusters

Abstract: DNA-stabilized silver clusters (AgN-DNAs) exhibit diverse sequence-programmed fluorescence, making these tunable nanoclusters promising sensors and bioimaging probes. Recent advances in the understanding of AgN-DNA structures and optical properties have largely...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
43
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(43 citation statements)
references
References 81 publications
0
43
0
Order By: Relevance
“…The 470 nm feature is atypically intense. 20 Furthermore, exciting in the 470 nm band yields green emission and a blue-shifted NIR emission (see Fig. 3A).…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…The 470 nm feature is atypically intense. 20 Furthermore, exciting in the 470 nm band yields green emission and a blue-shifted NIR emission (see Fig. 3A).…”
Section: Resultsmentioning
confidence: 97%
“…Which parameters affect the magnitude of the Stokes shift is not yet fully understood and a recent article by Copp et al tried to find systematic correlations in a large dataset, suggesting a link between cluster geometry and Stokes shift. 20,26,27 Monitoring the emission at 800 nm for DNA811-AgNC and 835 nm for DNA841-AgNC, the excitation anisotropy of the Fig. 1 Normalized absorption (at the 640 nm transition, T = 25 1C) and emission spectra (recorded at room temperature on a single molecule sensitive confocal microscope) 12 for (A) DNA841-AgNCs and (B) DNA811-AgNCs in a 10 mM ammonium acetate (NH 4 OAc), exciting at 640 and 645 nm, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Ag N -DNAs studied here were identified using high-throughput synthesis and characterization methods. 12 The DNA oligomer 5′-ATCTCCACAG-3′ stabilizes a species with an emission peak at 800 nm (800-Ag N -DNA), reported by Swasey et al 16 The oligomer 5′-GACGACGGAT-3′ stabilizes a species with peak emission at 760 nm (760-Ag N -DNA), reported in a large-scale study of Ag N -DNA excitation and emission spectra by Copp et al 3 Samples were purified by high performance liquid chromatography (HPLC) prior to characterization to ensure the presence of only one emissive species in solution ( Figures S1–S4 ).…”
mentioning
confidence: 93%
“…DNA strands of different sequences have yielded a diverse spectral palette of Ag N -DNAs with colors from 400 nm up to 1000 nm. 2 In conjunction with high fluorescence quantum yields (QYs), large Stokes shifts as compared to organic dyes, 2,3 and unique photophysics, 4,5 Ag N -DNAs are promising emitters for sensing 6 and biomedical imaging. 4,7,8 Studies have demonstrated that the silver nanocluster cores of fluorescent Ag N -DNAs can be rod-like.…”
mentioning
confidence: 99%